2011
DOI: 10.4103/1596-3519.87045
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemias in type 2 diabetes mellitus patients in Nnewi South-East Nigeria

Abstract: Dyslipidemia is highly prevalent among type 2 diabetic patients in Nigeria with the majority of the patients having combined dyslipidemia. We recommend that aggressive treatment of lipidemia and hyperglycemia can be instituted to reduce the risk of macro and microvascular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 14 publications
6
24
2
Order By: Relevance
“…[8] In another study, done by Jisieike-Onuigbo NN et al they found prevalence of dyslipidaemia to be 90.7%. [9] Similar study was done by Okafor CI et al, they found the prevalence of dyslipidaemia to be 89%. [10] A study conducted by Singh and Kumar also was consistent with findings of 59% type 2 diabetics having hypercholesterolemia and 53% had hypertriglyceridemia.…”
Section: Discussionsupporting
confidence: 68%
“…[8] In another study, done by Jisieike-Onuigbo NN et al they found prevalence of dyslipidaemia to be 90.7%. [9] Similar study was done by Okafor CI et al, they found the prevalence of dyslipidaemia to be 89%. [10] A study conducted by Singh and Kumar also was consistent with findings of 59% type 2 diabetics having hypercholesterolemia and 53% had hypertriglyceridemia.…”
Section: Discussionsupporting
confidence: 68%
“…Comparable study also done by Mwita in Dar es Salaam in 2009, the prevalence of dyslipidemia among the diabetic patients was 88% [16]. Within the African continent, similar studies have revealed high prevalence of dyslipidemia among diabetic patients; in Nigeria 82.6% to 90.7% from 2008-2011 respectively [8,9,10] and in South Africa [11]. Other areas such as Tehran and USA, similarly high prevalence of dyslipidemia was also observed 88.9% and 97% respectively [17,18].…”
Section: Discussionmentioning
confidence: 51%
“…Majority of the patients also had central obesity over 90%. Similarly in Gaborone [20] and South-East Nigeria [10] showed that overweight and obesity was strongly associated with elevated plasma lipid levels. A report in the National Health and Nutrition Examination Survey, 1999-2004, showed that the prevalence of dyslipidemia substantially increases with increased BMI [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,33,34,41,[47][48][49][50] Some of the few population studies we accessed in SSA compare prevalence in rural and urban populations. 23,34 Sabir et al documented significantly lower prevalence of dyslipidaemia among rural dwellers compared with urban non-hospital participants in Hausa-Fulani in north-western Nigeria.…”
Section: Discussionmentioning
confidence: 99%